Short review on the suitability of CFD modeling for Proton conducting fuel cell performance - Lidyayatty Abdul Malik; Ang, Lee Sin; Nafisah Osman; Oskar Hasdinor Hassan; Abdul Mutalib Jani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Electrochemical performance optimization of a conventional solid oxide fuel cell (SOFC) has been massively performed with computational fluid dynamic (CFD) modelling but it’s usage in a proton conducting fuel cell (PCFC) is still minimal. PCFC is a category of SOFC but with proton conductor as electrolyte instead of oxygen-ion conductor in a conventional SOFC. The fabrication of high electrochemical performance of PCFC is desirable because of its ability to operate at lower temperature. The objective of this short review study is to explore the possibilities of CFD modelling application to improve electrochemical performance of a PCFC system. Some CFD study that have been done to SOFC and PCFC were reviewed. One main finding from this short review is that the application of CFD modelling in PCFC design optimization is still minimal. There is a lack of studies that focus on the impact of PCFC anode microstructure on transport phenomena of the PCFC; for example on gas diffusion. It was also found that CFD modelling software Ansys Fluent with add-on Fluent SOFC module that is widely applied to conventional oxygen-ion SOFC need to be modify using User Defined Function (UDF) in order to be used in PCFC system.